A study on outcome of children with dengue infection and its clinical correlation with hepatidysfunction in a tertiary care hospital of Saurashtra - Mandal, Dhaneshwar Kumar; Shah, Sonal P.; Rathod, Hamendrasinh K.; Vaghela, Dhiman M. (International Journal of Contemporary Pediatrics, 2025)
Background: Dengue infection in children can significantly impact hepatic function, yet the spectrum of liver involvement and its correlation with disease severity needs further exploration in pediatric populations. Methods: A prospective observational study was conducted from July 2023 to July 2024 at a Guru Gobindsingh Government Hospital, Jamnagar in Saurashtra region, including 95 children aged 2 months to 12 years with suspected or confirmed dengue. Clinical assessments, dengue serology (NS1 antigen, IgM & IgG antibodies), liver function tests, coagulation profile, and complete blood counts were performed. The study evaluated hepatic dysfunction parameters and their correlation with disease severity. Results: Males and the 6-10 years age group were predominantly affected. Fever and petechial rash were the most common presentations. Laboratory findings revealed thrombocytopenia (67.3%), elevated total serum bilirubin (33.3%), raised SGPT (53.75%), elevated INR (6.3%), and low serum albumin (26.3%). Disease classification showed DF (87.4%), DHF (11.6%), and DSS (1.1%). The mortality rate was 1.1%, with one death due to DSS. Conclusions: Hepatic dysfunction in pediatric dengue presents a broad spectrum from mild enzyme elevation to severe hepatic failure. Significant liver enzyme elevation correlates with severe dengue manifestations. Seropositivity is associated with increased hepatic dysfunction and disease severity, emphasizing the importance of liver function monitoring in dengue management.